The Correlations of Advertising Exposure, Communication Competency of Ambassador, and Intensity of Peer Group Communication with Decision of Using Telkomsel Product - Hesty Puspita, Sayu; Herieningsih, MS, Dra. Sri Widowati (Interaksi Online, 2016)
Competition between cellular provider products in Indonesia is getting tougher. In order to maintain the existence and expanding market in the youth segment, Telkomsel do some marketing strategies like advertising in mass media and holding Ambassador Telkomsel programs on Senior High School level to influence the decision of youths in using Telkomsel products. In addition, other factor that can affect the decision of youths is peer group. This research is conducted to understand the correlation between advertisement exposure, communication competency of ambassador and communication intensity of peer group with decision of using Telkomsel products. Theories used in this research are Advertising Exposure Process, Communication Competency Theory and Group Pressures. This research had interviewed 100 senior high students in Semarang to fill the research questioner using accidental sampling method. Pearson correlation test analysis is used to test the research hypothesis. The result of hypothesis test demonstrate advertisement exposure significance value of 0,998 and Pearson correlation coefficient value of 0,000. Those numbers show that there is no correlation between advertisement exposures with the decision of using Telkomsel products. Further, the hypothesis test result demonstrate of communication competence of ambassador variable significance value of 0,005 and Pearson correlation coefficient value of 0,297 which show the existence of correlation between ambassador communication competence with the decision of using Telkomsel products. Then, the hypothesis test demonstrate communication intensity of peer group variable significance value of 0,005 and Pearson correlation coefficient value of 0,297. The result shows that there is no significant relation between communication intensity of peer group with the decision of using Telkomsel products.